Evaluation of a management platform for extended care of type 2 diabetes - Qing Zhou; Li Zou; Yan Gao; Guo-Hong Zhu (Diabetology & Metabolic Syndrome)
Abstract Objective This study aims to evaluate the efficacy of a diabetes chronic disease management platform in extended care for patients with diabetes. Methods A cohort of 150 patients with type 2 diabetes (mean age, 51 years) were selected and randomly assigned to an observation group and a control group, each comprising 75 participants, from September 2023 to September 2024. The control group received standard extended care, while the observation group received extended care integrated with the diabetes chronic disease management platform. The two groups were compared in terms of blood glucose levels, emotional state, self-management ability, and quality of life at discharge and three months after the intervention. Additionally, the incidence of hypoglycemia and hospital readmission within three months after discharge were recorded and analyzed. Results Three months after the intervention, both groups exhibited reductions in fasting blood glucose, 2-hour postprandial blood glucose, glycated hemoglobin, and scores on the Self-Rating Anxiety Scale and Self-Rating Depression Scale compared to discharge levels. However, the observation group had significantly lower values than the control group (p < 0.05). Scores on the Summary of Diabetes Self-Care Activities decreased in both groups compared to discharge levels, but the observation group had relatively higher scores (p < 0.05). Scores on the General Quality of Life Inventory-74 increased in both groups compared to discharge, with the observation group demonstrating significantly higher scores across all dimensions (p < 0.05). Additionally, the incidence rates of hypoglycemia and hospital readmission were lower in the observation group than in the control group (p < 0.05). Conclusion The diabetes chronic disease management platform improves the effectiveness of extended care interventions in managing blood glucose levels, emotional state, self-management ability, and quality of life in patients with diabetes, while also reducing the risk of hypoglycemia and hospital readmission after discharge.